1996
DOI: 10.1539/joh.38.6
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Solubility and In Vivo Toxicity of Indium Phosphide

Abstract: In Vitro Solubility and In Vivo Toxicity of Indium Phosphide: Isamu Kabe et al. Department of Preventive Medicine and Public Health, School of Medicine, Keio University—This study was designed to clarify the in vitro solubility and the in vivo basic toxicity of indium phosphide (InP). InP powder was clearly soluble in synthetic gastric fluid and quite insoluble in saline or synthetic lung fluid. Male ICR mice (SPF grade) were given InP at the doses of 0, 1,000, 3,000, and 5,000 mg/kg, intraperitoneally (i. p.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…This finding can be interpreted as indicating that ITO particles are dissolved to greater extent in the deep lung than IO, resulting in higher blood contents of indium in the ITO-exposed rats. Kabe et al 22) demonstrated that indium phosphide powder is clearly soluble in synthetic gastric fluid indicative of acidic pH, while the powder is insoluble in saline or synthetic lung fluid (Gamble solution). Dittmar et al 23) reported that when indium phosphide particles are exposed to Gamble solution, a complex dynamic interaction with the particle surface results in high levels of dissolved indium.…”
Section: Discussionmentioning
confidence: 99%
“…This finding can be interpreted as indicating that ITO particles are dissolved to greater extent in the deep lung than IO, resulting in higher blood contents of indium in the ITO-exposed rats. Kabe et al 22) demonstrated that indium phosphide powder is clearly soluble in synthetic gastric fluid indicative of acidic pH, while the powder is insoluble in saline or synthetic lung fluid (Gamble solution). Dittmar et al 23) reported that when indium phosphide particles are exposed to Gamble solution, a complex dynamic interaction with the particle surface results in high levels of dissolved indium.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the inhalation of hardly soluble hazardous particles, such as crystalline silica, asbestos, and so on, induces pneumoconiosis. In animal experiments, intra-tracheal instillation of indium compounds induces pneumonitis, proliferation of fibrous tissues, pulmonary fibrosis, and other lung diseases [3][4][5][6] . The results of our study are consistent with these information.…”
Section: Discussionmentioning
confidence: 99%
“…Until the early 1990's, there was little information on the toxic effects of indium on humans or animals. In the mid 1990's, intra-tracheal instillation studies of particles of compound semiconductors such as indium phosphide, indium arsenide and indium trichloride revealed that metal compounds containing indium had a strong potential to induce severe lung damage [2][3][4][5][6] . In 2003, Homma et al 7) disclosed a case of interstitial pneumonia in a 27-yr-old male worker engaged in the wet surface polishing process of indium-tin oxide (ITO) target plates, high-density plates made of very hard ceramics composed of indium oxide and tin oxide, which are used to laminate transparent electroconductive thin-film on flat displays and solar cells.…”
mentioning
confidence: 99%
“…Beginning in the mid-1990s, the authors’ institutions performed single or repeated intratracheal instillation experiments with fine particles of hardly soluble indium compounds such as indium phosphide (InP) and indium arsenide and found that these induce severe lung inflammation with fibrotic changes16 and have mild reproductive effects 7 8. The US National Toxicology Program (NTP) carried out an InP inhalation experiment for two years and concluded that there is clear evidence of carcinogenic activity of InP on the lungs in male and female rats and mice 9.…”
mentioning
confidence: 99%